An unusual case of mediastinal mass and bilateral nodules. (June 2014) - Wichmann, Charlotte Lilli Elena; Helmchen, Birgit; Weber, Achim; Wildi, Stefan; Carboni, Giovanni Luca
A 23-year-old woman presented with a mediastinal paraganglioma and multiple pulmonary chondromas following antral gastric resection for gastrointestinal stromal tumor. These tumors form the Carney triad, a rare disorder of unknown genetic background. First described in 1977, approximately 120 cases have been documented in the literature. The tumors do not harbor the specific c-kit or PDGFRA gene mutations often found in sporadic gastrointestinal stromal tumor. In most cases, gastric gastrointestinal stromal tumor is the first tumor to be detected, with secondary tumors appearing years later. Even if it is rare, Carney triad should be suspected in young patients with history of gastrointestinal stromal tumor.